POLŠTINA V JAZYKOVÉ KRAJINĚ OSTRAVSKÉ ZOO. - MURYC, JIŘÍ (Studia Slavica, 2024)
The purpose of this text is to present several aspects of language landscape research using the example of Zoological Garden and Botanical Park Ostrava. The Polish language in the linguistic landscape of ZOO Ostrava was analysed from a synchronic perspective using the author’s own field research, conducted in 2023–2024. The subject of the research were inscriptions (but also various types of voice messages and audio announcements of an in)formative or persuasive nature) in Polish found in the ZOO Ostrava area and recorded by the author of this text in the form of photographs and recordings. In order to collect materi)al for description and analysis, all signs in Polish on the outside of buildings, exceptionally also in their interiors were photographed, virtually all over ZOO area. Linguistic signs were analysed in accordance with the methodology adopted in linguistic landscape studies, and were divided into monolingual, polyphonic and mixed, as well as signs of public or private character.